Evaluasi Pemenuhan Standar Nasional Perpustakaan terhadap Perpustakaan Peserta Bimbingan Teknis Pengembangan Perpustakaan Sekolah/Madrasah - Widanarta, Dian; Tarigan, Anisa Kristiani (Media Informasi, 2025)
This study aims to evaluate the level of compliance with the National Library Standards (SNP 004:2024) by participants of the Technical Guidance on School/Madrasah Library Development, organized by the National Library of the Republic of Indonesia in 2024 across 19 provinces. The research employed a descriptive quantitative approach with an evaluative research design. The population consisted of all 1,804 participants of the technical guidance program, who were also used as the sample (total sampling). Data were collected using a library accreditation instrument based on six core components—collection, facilities and infrastructure, services, library personnel, administration, and management—and three supporting components: innovation and creativity, reading interest level, and the community literacy development index. The instrument was distributed online via Google Forms and analyzed quantitatively to determine the average scores and the extent to which the national standards were met, both overall and per component. The results indicate that only 315 respondents (17.46%) achieved scores above 60 and can be categorized as meeting SNP 004:2024, while 1,489 respondents (82.54%) still need to improve various aspects of library management. The component with the highest average score was library administration (53.51), whereas the lowest-scoring component was innovation and creativity (36.05). These findings suggest that administrative and institutional aspects are relatively better addressed than innovative program development. The results of this study are expected to serve as a foundation for future policy planning, capacity-building, and improvement efforts in school/madrasah libraries.